Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/gme.0b013e318230f3be
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term tibolone treatment on nuclear sex steroid hormone receptors and G-protein–coupled estrogen receptor-1 expression in the macaque uterus

Abstract: TIB treatment influences the protein expression of sex hormone receptors in monkey endometrium differently from that observed after conventional hormone therapy. We suggest that the observed differences in AR expression by TIB as compared with combined treatment may be of importance for endometrial atrophy as well as for the beneficial bleeding profile associated with this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In a study by Coyoy‐Salgado et al, 57 tibolone showed no effect on ERα, although it reduced ERβ in the cortex and hypothalamus but not hippocampus of rats fed a high‐fat diet. In the breast, both receptor types are not modified by tibolone, 58 whereas this compound increases ERα in the uterus 59 . Thus, although tibolone binds to ER, effects on receptor expression may be tissue‐, time‐ or dose‐dependent.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Coyoy‐Salgado et al, 57 tibolone showed no effect on ERα, although it reduced ERβ in the cortex and hypothalamus but not hippocampus of rats fed a high‐fat diet. In the breast, both receptor types are not modified by tibolone, 58 whereas this compound increases ERα in the uterus 59 . Thus, although tibolone binds to ER, effects on receptor expression may be tissue‐, time‐ or dose‐dependent.…”
Section: Discussionmentioning
confidence: 98%
“…To support this idea, it has been shown that: 1) estrogen receptor α predominates in the endometrium, whereas progesterone receptors A and B do in myometrium [ 20 ] ; 2) tibolone metabolite distribution varies among tissues, for example Δ 4 -tibolone (progestagenic/androgenic) is present in myometrium and vagina, and 3-α-hydroxytibolone (estrogenic) is found in serum from postmenopausal women treated with tibolone [ 21 ] ; and 3) within endometrium, depending on the cell type, tibolone may induce diff erent responses, such as the decrease of estrogen receptor-alpha mRNA and protein in stromal cells, and the induction of progesterone receptor mRNA in glandular cells [ 19 ] . Another plausible explanation to the lack of contractile response to serotonin in the uterine rings is that, besides 5-HTR 2A , tibolone may induce the expression of an inhibitory serotonin receptor subtype, which might counteract the 5-HTR 2A stimulatory eff ect.…”
mentioning
confidence: 88%